WRITING TASK ACTIVITIES IN DEVELOPING STUDENTS’ WRITING SKILL - Antoni, Rivi (Universitas Pasir Pengaraian, 2016)
This article is concerned with the study of applying writing task activities to students’ writing skill in developing good paragraphs at class II/A English Department in FKIP University of PasirPengaraian 20152016. The aspects explored in the study covered activities done by the lecturer in facilitating students’ need of the writing knowledge and skill . The research employed the action research design and the instruments used in collecting the data were a set of tests, observation sheet, fieldnoteand interview.The data analysis covered preparation and data implementation. The findings showed that thethe use of writing task activities could better improve students’ writing skill in developing good paragraphs. The finding also found somefactors that contributed to the better improvement, namely the selection of topics to be developed, the rule of peer and group discussion and the support of the writing lecturer in the instruction.